Rheological and emulsifying properties of an exopolysaccharide produced by potential probiotic Leuconostoc citreum-BMS strain. (15th March 2021) - Abid, Yousra; Azabou, Samia; Blecker, Christophe; Gharsallaoui, Adem; Corsaro, Maria Michela; Besbes, Souhail; Attia, Hamadi
Graphical abstract: Highlights: Functional properties of EPS-BMS from Leuconostoc citreum were assessed. EPS-BMS had pseudoplastic and liquid-like behaviors under different conditions. EPS-BMS showed great emulsifying properties in both neutral and acidic conditions. EPS-BMS could be used as a functional food ingredient for industrial applications. Abstract: EPS-BMS, is to our knowledge, the first high molecular weight exopolysaccharide from potential probiotic Leuconostoc citreum- BMS strain that consists on a mixture of α-(1, 6)-dextran branched at the third position and β-(2, 6)-levan. This sample exhibited interesting rheological and emulsifying properties under different conditions. Steady shear experiments proved that EPS-BMS had a pseudoplastic behavior without thixotropic properties. Interestingly, pseudoplasticity was maintained even under stress conditions of temperature, pH and salts, which could provide some sensory properties for food products such as mouth feel. Dynamic oscillatory measurements reflected a liquid-like behavior of the sample regardless of the studied EPS concentration, pH, temperature and ionic force. Results related to the emulsifying as well as interfacial properties showed that EPS-BMS had great potential to be applied as emulsifier and/or emulsion stabilizer in both neutral and acidic conditions. Based on the properties reported in this work, EPS-BMS could be potentially applied in the food industry.